Evaluation of humidity sensor based on PVP-RGO nanocomposites - Bhangare, Bhagyashri; Jagtap, Shweta; Ramgir, Niranjan; Waichal, Rupali; Muthe, K. P.; Gupta, S. K.; Gadkari, Sanjay C.; Aswal, D. K.; Gosavi, Suresh (IEEE sensors journal, 2018)
his paper describes the humidity sensing properties of one step in situ synthesized poly (N-vinyl pyrrolidone)- reduced graphene oxide (PVP-RGO) nanocomposites. Different PVP-RGO nanocomposites were obtained by varying PVP/GO weight %ratio as x/50 mg, wherein x = 25, 50, and 75 mg, respectively. The real-time adsorption kinetics of the water molecules during the humidity sensing were also discussed using Elovich model, pseudo first and second order equations. The increase in humidity response of 1.5 PVP-RGO nanocomposite is attributed to the presence of large amount of oxygen functionalities. The above observation was corroborated using spectroscopic analysis. The optimized PVP-RGO nanocomposite showed faster response kinetics with response and recovery times of 10 and 20 s, respectively. The present humidity sensor shows remarkable linearity over the range of 20-90%RH. More specifically, sensitivity was correlated with oxygen functionalities created due to variation of PVP during the functionalization of RGO nanosheets.